Determination of Demographic, Systemic, and Radiographic Characteristics of Patients Applied to the Oral and Maxillofacial Radiology Clinic - Taş, Ayşe; Yardimci, Selmi (UI Scholars Hub, 2024)
Objective: Anamnesis, extraoral intraoral examination, radiographic examination, and other special examination methods are used to diagnose diseases in the oral and maxillofacial regions. The aim of this study was to establish the demographic, systemic, and radiographic characteristics of the patients by analyzing the records of patients who were treated at the Oral and Maxillofacial Radiology Clinic of the University Faculty of Dentistry. Methods: The anamnesis and diagnostic records of patients who were treated at the OMR clinic between 01.01.2013 and 31.12.2019 and the radiographic records of the patients referred to the X-ray department were retrospectively analyzed. The number of patients was analyzed according to demographic, systemic, and radiographic classifications, and tables were created according to years and total numbers. Results: The number of females who applied between 2013-2019 was statistically significantly higher than that of males. When the age distribution of all patients who applied to the OMR clinic was analyzed, it was observed that the patients who applied were 15 years of age and older, and 29.3% of these patients were in the 30-44 age group, with the highest proportion. When radiographic data were analyzed, it was observed that the most common radiograph obtained was a panoramic radiograph (90%). Conclusion: Anamnesis records revealed the systemic disease characteristics of the study area, which is helpful for diagnosis and treatment planning. The most requested radiographic types and clinics that requested the most radiographs were determined. This will help improve the functioning within and between departments. By determining the common diagnoses in panoramic radiographs, the issues to be considered in patients of certain age and sex groups have been clarified.